Determinants of Safe Behavior among Clinical Pathology Assistants at Dr. Soebandi Regional Hospital Jember, Indonesia - Octaviani, Puspita; Hartanti, Ragil Ismi; Indrayani, Reny (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Every workplace has potential hazards that can threaten work safety, including clinical pathology laboratories. Work accidents in clinical pathology at Dr. Soebandi Regional Hospital Jember have decreased every year. This study aims to examine the determinants of safety behavior among clinical pathology assistants at Dr. Soebandi Regional Hospital, Jember. Methods: This research was a quantitative descriptive study with a cross-sectional approach. The study's respondents were 32 clinical pathology assistants. We collected data using a questionnaire. We analyzed this research using frequency, crosstab, and logistic regression tests. Results: The majority of clinical pathology assistants were under 40 years old, had completed occupational health and safety training, possessed competencies suitable for their work, maintained a positive attitude, and demonstrated high motivation at work. Almost all respondents stated that supervision was good, they had good knowledge, and their most recent level of education was Diploma-III. Most clinical pathology assistants behave safely. Clinical pathology assistants who are under 40 years old, have completed occupational health and safety training, exhibit competence, a positive attitude, and high motivation, report good supervision, possess good knowledge, and hold the latest Diploma-III education level are more likely to behave safely. Conclusion: Several clinical pathology assistants have demonstrated safe behavior while working in the clinical pathology laboratory. Several factors, including superior supervision and reasonable supervision efforts in the clinical pathology laboratory, contribute to the safe behavior of clinical pathology assistants.